Meningkatkan Karakter Disiplin Peserta Didik Melalui Materi Pancasila Menggunakan Metode Holistik di Sekolah Dasar - Widya Nanda Alifah; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve students' disciplinary character through Pancasila material using holistic methods. The holistic method has four important aspects, namely: mental, physical, emotional and spiritual. The results of this research show that the holistic method is very effective in improving students' disciplinary character. Students not only understand the principles of Pancasila cognitively, but can also apply the principles of Pancasila in everyday life. Students show an increase in discipline, responsibility and emotional control. This research shows that the holistic method can be an effective method for improving the disciplinary character of students through Pancasila material in elementary schools, which will make students become people who are balanced, have integrity, and are able to apply Pancasila values in everyday life.